Feed Intake and Growth Performance of Indigenous Chicks Fed Diets with Moringa oleifera Leaf Meal as a Protein Supplement During Early Brooding Stage - Gadzirayi , C.T.; Mupangwa, J.F. (International Journal of Poultry Science, 2014)
The high cost of conventional feed ingredients in poultry diets has necessitated the investigation into unconventional readily available feedstuffs. The study was designed to investigate the effects of feeding different levels of Moringa oleifera leaf meal (MOLM) on feed intake and growth performance of indigenous chicks. Eighty four unsexed indigenous chicks were assigned to four treatment diets, with each treatment being replicated three times. The dietary treatments were as follows; control diet (T1) without MOLM and diets containing MOLM were at the rate of 5% (T2), 10% (T3) and 15% (T4) to supplement the CP of the control diet. Chicks fed on 0% MOLM had a higher average weekly feed intake than the other three treatments (T2, T3 and T4). The highest weight gain was experienced between weeks 4 to 6 except for treatment 3 that had its peak weight gain on week 5. FCR was similar for all dietary treatments. Weekly live bird weight (WLBW) advantage of chicks fed 0% MOLM diet was maintained followed by those fed diet containing 5% MOLM. The chicks on 10 and 15% MOLM diet recorded similar, but significantly (p < 0.05) lower WLBW from the 5 to 8th week than chicks on 0-5% MOLM. The study recommended MOLM inclusion levels of 5% in chicken diets during early brooding stage.